Aplicação do modelo microbiano do metabolismo animal ao estudo da biotransformação de um potencial agente anti-hipertensivo - Guimarães, Telma de Matos (2013)
The " Microbial Models of Mammalian Metabolism" using filamentous fungi be used to study the biotransformation as an alternative to identify and product mammalian metabolites, with the goal of evaluate the profile of biotransformation of LASSBio 897, this This model was appliedto 3-thyenilidine-3,4-methylenedioxybenzoylhydrazide (LASSBio-897), a potential antihypertensive agent. The fungi Aspergillus alliaceus NRRL315, Beauveria bassiana ATCC 7159, Cunninghamella echinulata ATCC9244, NRRL1757 and Mortierela isabelina NRRL 1757 e Muccor plumbeus ATCC4740 were selected for the biotransformation LASSBio-897. The biotransformation was carried outin culture medium PDSM and Corn Steep at two different concentration sof the substrate.The monitoring of there action kinetics was done by methods thin layer chromatography (TLC) and high performance liquid chromatography(HPLC), separation and purification of the formed products was performed by colun chromatography (CC). Nuclear magnetic resonance (RMN) methods, mass spectrometry and spectroscopyin the region of Infrared (IR) assisted in the elucidation of the structure of the biotransformation products of LASSBio 897. We identified four metabolites in the reaction mixture and, based on information obtained by MS and NMR was proposed structure of 3-tienilidena-3,4-dihydroxybenzoilidrazine (Met. I), 1,3-benzodioxol-5-carboxamide (Met. II), 1, 3-benzodioxol acid (Met. III) and sulfoxide (Met. IV); A simultaneous study of the pharmacokinetics of LASSBio 897 in healthy Beagle dog indicated the presence of MET.I and II in dog serum confirming the importance of applying this model.to obtain metabolites mamalia.